Research status and application scenario analysis of high temperature superconducting cable - ZHU Jinhua; ZHU Hanshan; WANG Enzhe; CHEN Xiangrong (Zhejiang dianli, 2023)
High temperature superconducting （HTS） cable has the advantages of high transmission capacity， low line loss， small corridor area， safety and environmental protection， high power transmission and so on， which can solve the urgent power supply and demand relationship of urban power grid， the saturation of underground transmission and distribution corridor and other problems， and help achieve the national goal of "carbon emission peak and carbon neutrality". Firstly， the structure classification， advantages and laying modes of HTS cables are summarized. Secondly， the research status of HTS cable at home and abroad in the past 20 years and the key technologies in engineering application of HTS cables are emphatically introduced. Finally， the application scenarios of HTS cables are analyzed and predicted. The economy of superconducting transmission can be further improved by improving the technical standards and specifications， taking into account both AC and DC superconducting cable technology， which is expected to achieve the large-scale commercial application of superconducting cable and change the pattern of traditional power transmission.